Socio-cultural determinants of low back pain among hill and valley populations in Manipur, India: a cross-sectional study - Sanjoy, Akoijam; Singh, Sagolsem Adarsh (International Journal Of Community Medicine And Public Health, 2025)
Background: Low back pain (LBP) is a highly prevalent musculoskeletal disorder and a major public health concern worldwide. Beyond biological factors, socio-cultural determinants significantly influence the perception, response, and management of pain. In Manipur, India, the cultural and healthcare contexts of the hill and valley populations differ considerably, potentially shaping health-seeking behaviours and outcomes. Objectives were to compare socio-cultural factors influencing LBP among hill and valley populations of Manipur and to examine their healthcare-seeking behaviour. Methods: A hospital-based cross-sectional study was conducted in the department of PMR, RIMS, Imphal. A total of 80 adults with chronic LBP (>3 months) were recruited through purposive sampling. Data were collected using a semi-structured questionnaire covering socio-demographic characteristics, beliefs, and health-seeking behaviour. Chi-square test was applied to examine differences between groups. Results: LBP was more common among farmers in hill areas (41.2%), while private employees predominated in the valley (45.7%). Nearly half of the hill participants (47.1%) had no formal education, compared to 45.7% in the valley who studied only up to class V. Healthcare access was poorer in the hills, with 55.9% living ≥10 km from a health centre. Belief systems varied: hill participants often viewed LBP as divine punishment (44.1%), while valley respondents attributed it to evil spirits (47.8%). Overall, 76.3% avoided medical care, preferring quacks, rituals, or self-treatment. Conclusions: Socio-cultural beliefs, low education, poor healthcare accessibility, and occupational risks strongly shape LBP prevalence and care-seeking behaviour in Manipur. Culturally sensitive health education and improved healthcare access are critical for effective management.